E-Learning Readiness In The Employees Provident Fund (EPF) Malaysia - Hj.Marjumin, Hjh.Zanaria (2009)
This paper reports on the EPF employees\' readiness towards e-learning. The readiness report is derived from the EPF E-Learning Pilot Project conducted in the EPF.